Maternal exposure to difenoconazole-induced developmental defects and its mechanisms in F1 zebrafish (Danio rerio) - Ying Zhang; Fuqi Yang; Qian Zhang; Yunan Wu; Jiaolong Huang; Peng Duan; Xingjian Zhou (Ecotoxicology and Environmental Safety)
Difenoconazole (DFZ), a representative triazole fungicide, has become ubiquitously detectable in aquatic systems owing to its extensive agricultural utilization, potentially jeopardizing ecological health through bioaccumulation. Despite its environmental prevalence, intergenerational consequences following maternal DFZ exposure remain poorly characterized. Herein, we systematically examined F1 offspring developmental impacts by exposing maternal zebrafish to environmentally realistic DFZ concentrations (3, 30 and 300 μg/L) for 28 days (d). Comprehensive phenotypical and molecular assessments were subsequently performed on F1 progeny, incorporating physiological biomarkers evaluation, histological examination, transcriptomic profiling, and quantitative validation of dysregulated signaling pathways. Maternal DFZ exposure elicited multidimensional developmental impairments in F1 larvae, characterized by morphological anomalies including pericardial/yolk sac edema, diminished cardiac contraction frequency, as well as shortened body axis and reduced ocular dimensions. Furthermore, neurosensory dysfunction manifested through attenuated spontaneous motility and compromised motor coordination capacities. Transcriptomic profiling identified organ-specific transcriptional dysregulation: cardiac development (tbx5, nkx2.5, myl7, myh6 and vmhc), eye development (rhol, opn1mw4, opn1sw1 and opn1sw2), and neurodevelopment (ache, syn2a, manf, gap43, gfap, gpx4a and mbp) were abnormal in F1 larvae. RNA-Seq showed that the cardiac muscle contraction, heart morphogenesis, eye development, neuron differentiation, GABAergic synapse, skeletal system development and osteoclast differentiation signalling pathways were significantly enriched. Taken together, our results demonstrated that maternal zebrafish DFZ exposure at environmentally relevant concentrations potentially resulted in growth retardation and developmental disorders in F1 generation, providing new insight into the underlying maternal transfer effects.